What haunts us - Danan, Joseph (Tropelías: Review of Literary Theory and Comparative Literature, 2021)
Even in the face of theatrical performances that break with illusion, we sometimes find ourselves plunged into an almost hypnotic state. The question we will ask ourselves, drawing on Jérôme Bel’s Cour d’honneur and Romeo Castellucci’s Le Metope del Partenone, is this: how is the release of such shows? They can haunt us for a long time. Writing then appears as a means, not quite to get out of it, but on the contrary to prolong the spell by other means.